UY SHAROITIDA TOVUQLAR ARGAS PERSICUS KANALARIGA QARSHI KURASH USULLARI - Omonova , N.R. (Actual problems and prospects of the study of the fauna, 2024)
Currently, as in the rest of the world, poultry farming is successfully developing in Uzbekistan to ensure the population's food supply. However, one of the challenges hindering the development of this sector in both industrial and household poultry production is ectoparasitic diseases affecting birds. Among the diseases caused by arthropod ectoparasites in domestic poultry, especially chickens, the most dangerous is argasidosis. This disease in chickens is caused by the Persian tick, Argas persicus.